Historical education of primary school children: from theory to practice - Irina V. Verkhovykh; Natalya P. Shityakova; Inga V. Zabrodina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The relevance of the problem of historical education in primary school is determined by the need for younger students to develop a sustained interest in history, awareness of the importance of their own cultural and historical identity. This requires teachers to understand the essence of this process, apply innovative teaching methods and approaches aimed at actively involving students in learning history. The purpose of our research is to determine the essence of the concept of “historical education of primary school children” and the specifics of the organization of this process in primary school. Materials and methods. The following research methods are selected: 1) analysis of psychological and pedagogical literature – in order to determine achievements in solving the problem under consideration, to identify existing scientific points of view on the problem of historical education of younger schoolchildren; 2) SWOT analysis – in order to identify the advantages and disadvantages of existing programs aimed at historical education; 3) a survey – to determine the level of formation of knowledge of younger students about historical events. The sample of the study was made up of students of the 3rd and 4th grades of schools in Chelyabinsk. The sample size was 170 people. The analysis of psychological and pedagogical literature carried out by the authors allowed us to state the insufficient elaboration of the problem of historical education of younger schoolchildren in both domestic and foreign literature. The theoretical significance of the research lies in the author’s formulation of the concept of «historical education of primary school children», which refers to the activity of a teacher aimed at forming children’s initial historical knowledge in connection with an interest in the history of their Fatherland, a personal understanding of the significance of the main events, the desire to preserve historical memory. The analysis of the results of the survey indicates a lack of awareness of students in grades 3–4 about historical events. Based on the conducted SWOT analysis, threats to achieving the goals of historical education have been identified: excessive content of existing programs, planning a large number of expected results. Historical education in primary schools should be aimed at the study of reliable and scientifically based historical knowledge by children, the development of the ability to understand the causes and consequences of historical events, to assess their impact on people’s lives. It creates one of the foundations of the all-Russian civic identity and collective historical memory. One of the tasks of historical education in primary school is to form a value attitude to the world around us based on acquaintance with important and truly vivid events, personalities, and stories from the history of our country. To achieve this task, it is necessary to use the opportunities of lessons (literary reading, the outside world, ORCSE, music, art, etc.) and extracurricular activities (participation in design and research activities, visiting theaters, staging performances with a historical plot, studying epics, fairy tales, folk art, etc.).